Psychological distress among pharmacy students in Ghana and its impact on academic performance - Okyere, Harry A.; Wutor, Victor C. (International Journal of Research in Medical Sciences, 2025)
Background: Mental health encompasses emotional, psychological, and social well-being, shaping cognition, behaviour, and interpersonal relationships across the lifespan. There is a high level of stress, anxiety and depression among students of professional programs such as pharmacy. Academic distress is expected to be associated with high general anxiety. Methods: The study employed a quantitative cross-sectional design and used the depression, anxiety, and stress scale (DASS-21) to measure psychological distress and self-reported grade point average (GPA) for academic performance. A sample of 482 pharmacy students from three pharmacy institutions completed the online survey between April and July 2024. Results: Out of 497 participants, 482 completed the study, yielding a 97% completion rate. Of these, 50.6% were female (n=244) and 49.4% male (n=238). Most students (46.9%) were aged 21-24, about a quarter below 21 years, while the fewest were 30 or older. The majority were Christians (86.3%), followed by Muslims (12%), with a small proportion from other faiths. About 80% (n=386) of respondents reported symptoms of depression, anxiety and stress. Both males and females showed similar levels of anxiety and depression. However, females had a 37% higher likelihood of reporting stress than their male counterparts (OR=0.73, p=0.002). Conclusions: This study revealed a high prevalence of anxiety, depression, and stress among pharmacy students in Ghana, with female students particularly prone to stress. While anxiety and depression correlate positively with higher academic performance, stress shows a negative impact.